Fast wave interferometer for ion density measurement on DIII-D. (1st January 2022) - Akiyama, T.; Boivin, R.L.; Brookman, M.W.; Degrandchamp, G.H.; Heidbrink, W.W.; Muscatello, C.M.; Pinsker, R.I.; Thome, K.E.; Van Compernolle, B.; Van Zeeland, M.A.
Abstract: A fast wave interferometer (FWI), which can measure ion mass density, has been developed on DIII-D for its use on future fusion reactors, as well as for the study of ion behavior in current plasma devices. The frequency of the fast waves used for the FWI is around 60 MHz, and require antennas and coaxial cables or waveguides, which, unlike traditional mirror-based optical interferometers, are less susceptible to neutron/gamma-ray radiation and are relatively immune to impurity deposition and erosion as well as alignment issues. The bulk ion density evaluated using FWI show good agreement with that derived from CO2 interferometry within about 15%. When the ion mass density measurement by FWI is combined with an electron density measurement from CO2 interferometry, Z eff measurements are also enabled and are in agreement with those from visible Bremsstrahlung measurements. Additionally, large-bandwidth FWI measurements clearly resolve 10–100 kHz coherent modes and demonstrate its potential as a core fluctuation diagnostic, sensitive to both magnetic and ion density perturbations.